The artifacts of Tikal : utilitarian artifacts and unworked material - Moholy-Nagy, Hattula (University Museum monograph, 2003)
Occupied continuously for 1,500 years, Tikal was the most important demographic, economic, administrative, and ritual center of its region. The collection of materials recovered at Tikal is the largest and most diverse known from the Lowlands.This book provides a major body of primary data. The artifacts, represented by such raw materials as chert and shell are classified by type, number, condition, possible ancient use, form, material, size, and such secondary modifications as decoration and reworking, as well as by spatial distribution, occurrence in the various types of structure groups, recovery context, and date. The same format, with the exception of typology, is used for unworked materials such as mineral pigments and vertebrate remains.While few artifact reports go beyond a catalog of objects organized by type or raw material, this report puts the materials into their past cultural contexts and thus is of interest to a wide range of scholars.Content of this book's CD-ROM may be found online at this location: http://core.tdar.org/document/376593.University Museum Monograph, 118.